ISLAMIC FINANCIAL LITERACY AS AN IMPROVEMENT IN THE QUALITY OF ISLAMIC BANK - Rahmayati, Rahmayati; Sihotang, Mutiah Khaira; Kurnia, Efry (Proceeding International Seminar of Islamic Studies, 2022)
Islamic financial literacy is a problem that still occurs in the existence of Islamic banking, so that in-depth studies continue to be carried out to determine the effectiveness of Islamic financial literacy on the quality of Islamic banks. The purpose of this study is to determine Islamic financial literacy can improve the quality of Islamic banks. The research method uses a qualitative approach from various reference sources and literature related to this research theme. The results of the study confirm that there is a link between Islamic financial literacy and the quality of Islamic banks from various previous studies that support this research.